A method for adjusting aggregation size based on acknowledgement (ACK) bitmap - Othman, Mohamed; Saif, Anwar (2012)
The present invention relates to a method for adjusting aggregation size based on Acknowledgement (ACK) bitmap, characterized by the steps of: receiving kth Compressed Block Acknowledgement (CBA); calculating granularity factor (g) by applying Equation (1); determining bit error density (BEDk) for kth CBA by applying Equation (2); receiving (k+1)th CBA; determining bit error density (BED(k+1)) for (k+1)th CBA by applying Equation (2); adjusting the aggregation size based on the value of granularity factor (g), kth bit error density BEDk values and (k+1)th bit error density BEDk+1; wherein if the kth bit error density BEDk is greater than the (k+1)th bit error density BEDk+1, then increasing the aggregation size based on the value of granularity factor (g); wherein if the kth bit error density BEDk is lower than the (k+1)th bit error density BEDk+1 then decreasing the aggregation size based on the value of granularity factor (g); wherein if the kth bit error density BEDk is equal to the (k+1)th bit error density BEDk+1 then the aggregation size is kept unchanged.